EFEKTIVITAS BIOENKAPSULAN Metarhizium anisopliae SEBAGAI UMPAN PAKAN UNTUK PENGENDALIAN HAMA Oryctes rhinoceros PADA MEDIA SERBUK GERGAJI DAN PUPUK KANDANG - Aziz, Miftah Lutfi Abdul; Hendarti, Indri; Apindiati, Rita Kurnia (Jurnal Sains Pertanian Equator, 2025)
One of the problems in oil palm cultivation is the attack of rhinoceros beetles (Oryctes rhinoceros) which can cause a decrease in oil palm production and productivity. Control of rhinoceros beetles can be done in various ways, one of which is biologically with the fungus Metarhizium anisopliae.This study aims to determine the effectiveness of the bioencapsulation (coating) of the fungus M. anisopliae in sawdust and manure compost media as feed bait in controlling O. rhinoceros pests. This study was conducted from February 27, 2024 to October 25, 2024 at the Plant Pest Laboratory, Faculty of Agriculture, Tanjungpura University using the Completely Randomized Design method with 6 levels, the treatment was repeated 5 times that the total units observed in this study were 30 units, 1 research unit contained 10 O. rhinoceros larvae, with the number of larvae tested being 300. The results showed that administering M. anisopliae bioencapsulant to second and third instar O. rhinoceros larvae was effective at a concentration of 108 conidia/ml. This bioencapsulant was able to control the population up to 82% in sawdust compost media (A4) and 76% in cow manure compost media (A5) within 12 days at a dose of 17 g per 10 larvae.